A Notary’s Authority In Issuing Copies of Acts From Minutes of Deeds of Other Notaries’ Protocol Parts - Elok Nadhiro (Faculty of Law, Merdeka University Surabaya, 2019)
Everyone needs evidence to prove the existence of a right or event, especially written evidence in the form of an authentic deed. Authentic deed is a deed in the form determined by law, made by or in front of the general employee in charge where the deed is made. One of the General Officers who makes authentic deeds is a Notary who has the obligation to make a deed in the form of a deed and keep it as part of the Notary Protocol. In the interests of proof for the parties, the Notary is obliged to issue a copy of the deed of the Minuta deed of the Notary Protocol. The deposit obligation does not only apply to the Minuta deed made by and / or in the presence of the notary concerned, but also to other Notary Protocols that he receives either because the other notary dies, has expired, or other causes.